PENGUKURAN KINERJA BALANCED SCORECARD (STUDI KASUS PADA PT. TELKOM INDONESIA TBK., WITEL SUMATERA UTARA) - Putri, Nadilla Vidya; Daud, Rulfah M. (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study's purpose is to analyze company performance from a customer, internal business process, learning and growth, and financial perspectives using the balanced scorecard approach at PT. Telkom Indonesia Tbk., Witel North Sumatra. The sampling method used is purposive sampling. The number of employee and customer/consumer respondents taken for this study were 44 and 78 respectively. The results showed the company's performance PT. Telkom Indonesia Tbk., Witel Sumatera Utara on a good customer perspective (mean 3.90) with a BSC score of 78.00%, on a very good internal business process perspective (mean 4.57) with a BSC score of 91.40%, on a very good learning and growth perspective (mean 4.44) with a BSC score of 88.80%, and in a good financial perspective with a BSC score of 209.80%. The results showed that the total BSC score was 468.00%. This means that the performance achievements of the Customer, Internal Business Process, Learning and Growth, and Financial Perspective exceeded the target.